Wearable chest sensor for stride and respiration detection during running - Bernhart, S.; Harbour, E.; Kranzinger, S.; Jensen, U.; Finkenzeller, T. (Sports Engineering, 2023)
Endurance running is among the most popular physical activities partially due to its low barriers to entry. However, some people avoid running because of respiratory distress, and respiratory monitoring could help prevent this. Wearable sensors are valuable for respiration detection during exercise and enable respiratory feedback in real time. Therefore, this study presents a wearable chest-mounted stride and respiration sensor including step and flow reversal event detection algorithms. The algorithms were evaluated using precision and recall between detected and reference events with respect to different levels of breathing depth, motion artifact, thoracic skin temperature and sweat. Overall F1 scores reached 93.2%, 97.4% and 97.2% for step, expiration and inspiration events, respectively. No significant effect on event detection performance was observed for breathing depth, stride motion artifact, or thoracic skin temperature. In contrast, sweat level slightly decreased detection performance. Consequently, this sensor is able to accurately measure stride and respiration during running and could be suitable for use as a system to guide runners` respiration during exercise.